2012
DOI: 10.1099/mic.0.053355-0
|View full text |Cite
|
Sign up to set email alerts
|

Fis regulates the competitiveness of Pseudomonas putida on barley roots by inducing biofilm formation

Abstract: An important link between the environment and the physiological state of bacteria is the regulation of the transcription of a large number of genes by global transcription factors. One of the global regulators, Fis (factor for inversion stimulation), is well studied in Escherichia coli, but the role of this protein in pseudomonads has only been examined briefly. According to studies in Enterobacteriaceae, Fis regulates positively the flagellar movement of bacteria. In pseudomonads, flagellar movement is an imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
47
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 79 publications
2
47
0
Order By: Relevance
“…Switching from planktonic to sessile growth requires reorganization of bacterial physiology and thus the expression of a large number of genes is changed during the process of attachment to abiotic or biotic surfaces (Mathesius, 2009;Matilla et al, 2007Matilla et al, , 2011Ramos-González et al, 2005). Indeed, we have shown that the global regulator Fis (factor for inversion stimulation) is involved in Pseudomonas putida PaW85 biofilm formation (Jakovleva et al, 2012). In addition, Fis reduces motility and recolonization of new areas on barley roots, showing that Fis is involved in the regulation of P. putida sessile and planktonic lifestyles (Jakovleva et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Switching from planktonic to sessile growth requires reorganization of bacterial physiology and thus the expression of a large number of genes is changed during the process of attachment to abiotic or biotic surfaces (Mathesius, 2009;Matilla et al, 2007Matilla et al, , 2011Ramos-González et al, 2005). Indeed, we have shown that the global regulator Fis (factor for inversion stimulation) is involved in Pseudomonas putida PaW85 biofilm formation (Jakovleva et al, 2012). In addition, Fis reduces motility and recolonization of new areas on barley roots, showing that Fis is involved in the regulation of P. putida sessile and planktonic lifestyles (Jakovleva et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, we have shown that the global regulator Fis (factor for inversion stimulation) is involved in Pseudomonas putida PaW85 biofilm formation (Jakovleva et al, 2012). In addition, Fis reduces motility and recolonization of new areas on barley roots, showing that Fis is involved in the regulation of P. putida sessile and planktonic lifestyles (Jakovleva et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations